Halal standards globally: a comparative study of unities and diversities among the most popular Halal standards globally - E Azam, Md Siddique; Abdullah, Moha Asri (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2021)
The global Muslim community, with its fastest-growing size, has made the global halal industry to become one of the fastest-growing markets in the world. The industry, as of 2018, with its significant annual growth rate, has a global market value of US$2.2 trillion. However, a number of inhibitors have slowed down the growth rate of the industry. One of the pressing issues within the halal industry is the lack of a universal halal standard. There are many halal standards that exist globally, and they vary from country to country. For example, Malaysian Standard, Halal standards by Standards and Metrology Institute for Islamic Countries (SMIIC), Halal Standard of Indonesia, United Arab Emirate (UAE), Brunei, Singapore, Pakistan, and others. Some of these standards are widely recognised and acknowledged by many countries across the world. Hundreds of Halal Certification Bodies (HCBs) of many countries are using these standards as reference for halal certification after getting recognised by the respective organization. Additionally, the number of applications by HCBs is increasing globally due to the rising demand for halal products and services. Most of these HCBs have received recognition from more than one accrediting bodies. This is because of the consumer trust and reliability on different standards. A lot of commonalities are observable amongst these standards because of the same primary source of Islamic law, i.e. Al-Quran and Al-Hadith. On the other hand, a significant gap or diversity is found in the implementation of the definition of halal and halal standards globally. Such diversity and differences in these standards have become a major obstacle of market entry by the industry players and Small and Medium Enterprises (SMEs) to expand their business. In this regard, a universal halal standard is crucial as the global halal industry targets the same consumers (Muslim population) to meet their faith-based needs. To address this issue, the foremost important step to be taken is to identify and realize the commonalities and differences among these halal standards globally. Simultaneously, it is also needed to know the factors of creating similarities and diversities. Such realization will enable the policymakers and Islamic scholars to come forward and work together to develop a universal halal standard globally. The objective of this paper is to critically analyse this matter by investigating the four most popular halal standards, which are the standards of SMIIC, Malaysia, Indonesia, and Singapore. To achieve the objective, this paper adopts the methodology of content analysis by reviewing the literature on halal standards globally. Additionally, the four most popular halal standards were investigated to realize the commonalities and differences. This study will be the first to compare the halal standard of SMIIC with other well-established halal standards globally. Interviewing Islamic scholars from different countries for respective standards was beyond the scope of the study because of time and other constraints.